THE IMPACT OF FINANCIAL TECHNOLOGY ON ISLAMIC BANKING SERVICES IN INDONESIA - Ratri Diana; Memet Slamet; Naelul Azmi; Choirunnisak; Rahardi Mahardika (PT. Cadas Insan Madani, 2026)
The rapid advancement of Financial Technology (FinTech) has significantly transformed the financial services industry, including the Islamic banking sector in Indonesia. The integration of digital technologies into Islamic banking has created new opportunities to improve financial inclusion, operational efficiency, customer satisfaction, and the accessibility of Sharia-compliant financial services. However, the adoption of FinTech also presents challenges related to cybersecurity, regulatory compliance, digital literacy, and adherence to Islamic financial principles. This study aims to analyze the impact of Financial Technology on Islamic banking services in Indonesia by examining its influence on service quality, customer experience, operational performance, and institutional competitiveness. The research employs a qualitative library research approach by reviewing scholarly articles, books, government reports, and publications from financial regulatory institutions related to FinTech and Islamic banking. The collected data were analyzed using descriptive content analysis to identify major trends, opportunities, and challenges in the digital transformation of Islamic banking. The findings indicate that Financial Technology has contributed positively to the modernization of Islamic banking services through the implementation of mobile banking, internet banking, digital payment systems, peer-to-peer financing, artificial intelligence, and blockchain technology. These innovations have enhanced transaction efficiency, expanded financial access, and strengthened customer engagement. Nevertheless, the study also identifies several obstacles, including cybersecurity risks, regulatory adaptation, digital infrastructure disparities, and the necessity of maintaining Sharia compliance in technological innovation. The study concludes that the successful integration of Financial Technology into Islamic banking requires collaboration among financial institutions, regulators, technology providers, and Sharia supervisory authorities to ensure sustainable, secure, and Sharia-compliant digital financial services. This research contributes to the growing literature on digital transformation in Islamic finance and provides recommendations for strengthening the competitiveness of Islamic banking in the digital era.